Antioksidan daun mensirak (Ilex cymosa) dan potensinya sebagai stimulan kematangan gonad ikan Cempedik (Osteochilus spilurus) - Mustobi Prananda; Destra Ramadhanu; Rahmad Hidayat; Teguh Firnanda; Ahmad Fahrul Syarif (Jurnal Akuakultur Sungai dan Danau, 2023)
Cempedik fish (Osteochilus spilurus) is one of the local fish species that has important economic value as a consumption fish. However, its existence in nature during the dry season is difficult to obtain so that research is needed to increase its population by accelerating gonad maturity. Mensirak leaves are one of the natural sources of antioxidants and can be used as a natural stimulant for cempedic fish gonad maturity. This study aims to determine the phytochemical content and antioxidant power of ethanol extract of mensirak leaves (Ilex cymosa) to accelerate the maturity of Cempedik fish gonads. The results of the study showed that mensirak leaves contained tannins, flavonoids and saponins in phytochemical testing and the presence of very strong antioxidants with IC50 values <50 ppm, which amounted to 25.29 µg/ml. The average value of GSI with treatment using mensirak extract is 0.0656% and treatment without using mensirak extract is 0.0491% with gonad maturity level III and IV.